Pengaruh PBV, NPM Dan Mvaterhadap Return Saham pada Perusahaan Sub Sektor Properti dan Real Estate di Bursa Efek Indonesia Periode 2015-2018 - nur komalasari; Sri Suartini (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This study aims to analyze the effect of Price to Book Value, Net Profit Margin and Market Value Added on stock return in real estate and property su-sector companies on the Indonesia Stock Exchange 2015 – 2018. The sample used is 17 companies of property and real-estate listed on the Indonesia Stock Exchange from 2015 to 2018. Observations using purposive sampling technique as a sampling method. The data used are secondary data and the analysis method used is the classical assumption test, multiple linear regression analysis, the coefficient of determination, the f test and t test. This study uses the assistance of the SPSS version 20.0 program in data processing. The results showed that only the variables Price to Book Value, Net Profit Margin and Market Value Added either simultaneously or partially had no effect on stock returns. These results indicate that Price to Book Value, Net Profit Margin and Market Value Added cannot be used as an inside mold determine the investment strategy of investing their shares in capital market. Keywords : Price to Book Value, Net Profit Margin, Market Value Added, Stock Return.